Digital Ecosystems of Organizations - O. E. Kalenov (Вестник Российского экономического университета имени Г. В. Плеханова)
Today we witness the rise of a new type of economy i.e. digital economy, whose foundation is formed by digital ecosystems. The article deals with the idea of digital ecosystems, specific features of their founding and developing. The author describes the pre-conditions of their emergence, which include the development of technology, customer’s desire to meet his/her needs in full and with minimum efforts, the necessity to eliminate geographic barriers and the ambition of business to get bigger profit at the expense of providing extra goods and services to the customer. The article studies the borders, structure and key elements of digital ecosystem. Special role is assigned to the organization – leader. The author shows a scheme of interaction of the customer and the platform and describes the mechanism of transforming data into knowledge in the interaction process. The author puts forward three approaches to shaping digital ecosystems: the development of own services, purchasing of outside ones and partnership agreements. The biggest in the world American and Chinese digital ecosystems were analyzed: Google, Apple, Facebook, Amazon, Alibaba and Tencent. The home experience of building digital ecosystems was investigated, such finance organization as Sber, Tinkoff Bank, VTB and companies Yandex, Mail Group and MTS were discussed. It makes it possible to draw a conclusion that Russian market of ecosystems is still on the stage of shaping, but it has positive prospects of integrating into digital economy being built.